Uruguay : 2007 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Uruguay. (IMF Staff Country Reports; Country Report ;, 2008)
Sound policies and favorable external conditions have led to a strong economic recovery, but important challenges lie ahead. Uruguay's near-term economic prospects are generally favorable. The main short-term challenge is rising inflation in the wake of vigorous growth and capital inflows. The reduction of vulnerabilities in recent years has been a major accomplishment, but challenges remain. The objectives and instruments of monetary policy should be clarified. Maintaining high primary fiscal surpluses is essential to reduce the debt burden. Further improving the business climate is key.